Pembelajaran PAI di Masa Pandemi Covid-19: Analisis Sebuah Metode dan Dinamikanya di Sekolah Dasar - Mariadi Mariadi; Surawan Surawan (Departement of Mathematics Education, 2023)
This study aims to find out how the PAI learning method is at SDN Tahai Baru 2 and SDN Tahai Jaya 1, Maliku District, Pulang Pisau Regency. This type of research is descriptive qualitative research. This research was conducted in 2 (two) State Elementary Schools (SDN) located in Maliku District, Pulang Pisau Regency, namely Tahai Baru 2 Elementary School and Tahai Jaya 1 Elementary School. The subjects in this study were PAI teachers at Tahai Baru 2 Elementary School and Tahai Jaya Elementary School. 1. Data collection techniques use interviews, observation and documentation, while data validation uses source triangulation. The results showed that the PAI learning method used at SDN Tahai Baru 2 and SDN Tahai Jaya 1, Maliku District, Pulang Pisau Regency was different, at SDN Tahai Baru 2 using 2 methods because the learning was done only through the WhatsApp application, the methods used were the lecture method and the assignment. Whereas at SDN Tahai Jaya 1 using 3 methods because the learning uses a blended learning model, the methods used are the lecture method, the drill method, and the assignment method. The inhibiting factors in learning PAI at SDN Tahai Baru 2 and SDN Tahai Jaya 1 Maliku District, Pulang Pisau Regency, namely, some parents do not have android cellphones, some parents do not understand the material and assignments given by the teacher, the lack of ability of parents of students to operate a cellphone, can't ask questions directly to the teacher, the network is sometimes unstable, and students don't like online learning. The supporting factors in PAI learning at SDN Tahai Baru 2 and SDN Tahai Jaya 1, Maliku District, Pulang Pisau Regency, namely, the enthusiasm of students to learn, buying laptops and data packages for teachers so they can prepare lessons well, student cohesiveness when getting assignments, Package book facilities are sufficient for students, parents accompany students while studying, and learning is more flexible.